Sex Education in Christian Religious Education Using an Instructional Approach and Desire Theology - Evani April Rama Sinurat (CV. Rayyan Dwi Bharata, 2022)
Sex education is still considered taboo for adolescence to discuss for some groups. Sex education is also one way to reduce or prevent sexual behavior problems. The purpose of this study is to gain an understanding that sex education can be provided holistically through the learning of Christian Religious Education, to find an increase in the understanding of students of Mentari Intercultural School Bintaro about sex education, and to show that the learning of Christian Religious Education can touch various aspects such as, biological, sociological, psychological, and theological. The research method that can be used this time is the Classroom Action Research method or commonly known as Classroom Action Research. The results showed that Christian Religious Education Learning using an Instructional Approach and Theology of Desire for Students of SMP Mentari Intercultural School Bintaro has succeeded in providing benefits in sex education.